STATUS NUTRISI PASIEN GAGAL GINJAL KRONIS DENGAN DIABETES MELLITUS DAN NON-DIABETES MELLITUS - Diyah Candra Anita (MEDIA ILMU KESEHATAN, 2016)
Background:Malnutrition is a common problem in chronic renal failure (CRF) patients with or without Diabetes Mellitus (DM). An assessment of nutritional status in CRF patients is encouraged to see the level of its severity. The general parameters for assessing nutritional status are serum albumin and hemoglobin. Objective:The objective of this research was to investigate the differences on thenutritional status of CRF patients with Diabetes Mellitus (DM) compared to those without DM at PKU Muhammadiyah Hospital Yogyakarta. Methods:This was a comparative descriptive research applying accidental sampling and was conducted for 6 months (June-November 2014). The main measuring devices were patients’ medical records and laboratory results of albumin and hemoglobin levels. Sampleof this study consisted of 30 respondents. Independent t-test was applied to analyze the differences of albumin and hemoglobin levels in both groups. Result:The test result showed that the albumin (p=0.917) and hemoglobin levels (p=0.168) of CRF patients without DM and that of CRF patients with DM were not significantly different. Conclusion:CRF patients with and without DM had low level of albumin and hemoglobin. Nurses shouldbe more careful in regulating fluidbalance to reduce pulmonary edema. Keywords: Chronic Renal Failure (CRF), diabetes mellitus(DM), albumin, hemoglobin